PKN1 Is a Novel Regulator of Hippocampal GluA1 Levels - Safari, Motahareh Solina; Obexer, Dido; Baier-Bitterlich, Gabriele; zur Nedden, Stephanie (Frontiers in Synaptic Neuroscience, 2021)
Alterations in the processes that control α-Amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor (AMPAR) expression, assembly and trafficking are closely linked to psychiatric and neurodegenerative disorders. We have recently shown that the serine/threonine kinase Protein kinase N1 (PKN1) is a developmentally active regulator of cerebellar synaptic maturation by inhibiting AKT and the neurogenic transcription factor neurogenic differentiation factor-2 (NeuroD2). NeuroD2 is involved in glutamatergic synaptic maturation by regulating expression levels of various synaptic proteins. Here we aimed to study the effect of Pkn1 knockout on AKT phosphorylation and NeuroD2 levels in the hippocampus and the subsequent expression levels of the NeuroD2 targets and AMPAR subunits: glutamate receptor 1 (GluA1) and GluA2/3. We show that PKN1 is expressed throughout the hippocampus. Interestingly, not only postnatal but also adult hippocampal phospho-AKT and NeuroD2 levels were significantly elevated upon Pkn1 knockout. Postnatal and adult Pkn1-/- hippocampi showed enhanced expression of the AMPAR subunit GluA1, particularly in area CA1. Surprisingly, GluA2/3 levels were not different between both genotypes. In addition to higher protein levels, we also found an enhanced GluA1 content in the membrane fraction of postnatal and adult Pkn1-/- animals, while GluA2/3 levels remained unchanged. This points towards a very specific regulation of GluA1 expression and/or trafficking by the novel PKN1-AKT-NeuroD2 axis. Considering the important role of GluA1 in hippocampal development as well as the pathophysiology of several disorders, ranging from Alzheimer’s, to depression and schizophrenia, our results validate PKN1 for future studies into neurological disorders related to altered AMPAR subunit expression in the hippocampus.